Cognition, creativity, and entrepreneurship - Ward, Thomas B. (Journal of Business Venturing, 2004)
Cognitive approaches to creativity are discussed as they relate to an important task of entrepreneurs: generating novel and useful ideas for business ventures. Attention is given to the paradoxical role of knowledge, which can either enhance of inhibit creativity, as well as to the properties of knowledge and a selected set of processes that influence the originality of newly generated ideas. Experimental findings are discussed along with suggestions about how those findings might be translated to practical applications.